STUDENTS’ DIFFICULTIES IN WRITING PROCESS OF RECOUNT TEXT FOR EIGHT GRADE OF JUNIOR HIGH SCHOOL - Stevani Simanjorang; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
Writing is very important and most required in academic field. Students Writing is the process of describing a language so that the message conveyed by the writer can be understood by the reader. Kingston (2002:3) state that student’s achievement in learning English is only measured by the productive skills, especially the writing performance. Writing is one way to express ideas, experiences and feelings in written form. This study aims to determine the difficulties experienced by students when writing recount text in junior high schools. This research was conducted by analyzing students dffculties in recount text according to the theory of Heong et al. (2012) and the factor of students difficulties by Zaenudin (2015: 10) state that these factors include: (a) their lack of fluency in issuing ideas using English. (b) they are not accustomed to using English in daily communication, (c) lack of understanding of students about the generic struscture and language feature, (d) lack of their ability to think abstractly. Data sources were two eighth grade students in one school. Junior High School (SMP) in Sidikalang, Indonesia. Data collection techniques by observation and interviews. The data analysis technique is descriptive analysis. The data obtained will be analyzed using the analysis procedure by Flower and Hayes (1981). According to Flower and Hayes (1981), cognitive process analysis to gather student protocols will be given the opportunity to write recount texts with different themes and then ask them to write out loud near the tape recorder, and ask students to think and write, they are asked to say everything that comes to their mind as they write, including distorted ideas, false starts, and incomplete or fragmented thinking. writers are not asked to get involved or analyze themselves when writing, but only to think hard when writing like people who talk to themselves. The findings obtained are: difficulties experienced by students, namely difficulty generating ideas and difficulty organizing ideas, and the factors that influence these difficulties are students' lack of understanding of themes, language features and general structures, b. Students are not fluent in expressing ideas using English, Students are not used to using English in daily communication, d. Low student interest and motivation in writing English.Keywords: Difficulty, Writing, process, Recount text, Student